Advance in prostate cancer biomarker discovery: bridging detection, prognosis and therapeutics - Subhayan Das; Shayeri Chatterjee Ganguly; Shiuli Bera; Moumita Kundu (Discover Oncology)
Abstract Prostate cancer is the second leading malignancy in males. Prostate cancer can be easily curable if it is diagnosed at an early stage. The prognosis of patients with metastatic or resistant cases can also be improved if adequately characterized with biomarkers. Prognostic and predictive biomarkers are crucial for the prediction of therapeutic response of prostate cancer patients. This article discusses various diagnostic, predictive, and prognostic biomarkers for this cancer. It also highlights the limitations of existing biomarkers and the challenges in novel biomarker discovery for prostate cancer. Moreover, this article emphasizes the application of genomics and epigenomics to discover novel prostate cancer biomarkers. Recent research to explore potential biomarkers for this disease has been reviewed here. Understanding the tumor immune microenvironment is vital for adequately diagnosing tumor tissues and predicting prognosis and therapeutic outcomes. Immune checkpoint markers are also discussed here. The current status of tumor microenvironment-based research for biomarker discovery has been explained in this article, highlighting its potential for novel biomarkers that can be employed in clinical settings. Graphical abstract